722 Patients' and family members' involvement in management of violence in mental health care. (1st September 2016) - Lantta, Tella; Kontio, Raija; Anttila, Minna; Kauppi, Kaisa; Välimäki, Maritta
Abstract : Background: Patient violence in mental health care is a widely recognised hazard for staff members. It causes burden also for the patients and their family members. In recent years, patients and their family members have been encouraged to take a more active role in the planning and delivery of health care. Therefore it is important to involve these groups also to development of novel methods for preventing and managing violence in psychiatric care. Methods: Four focus group interviews were conducted among members (n = 9) of mental health patients' association and members (n = 8) of associations for families of mental health patients. This study aimed to explore participants' ideas how to prevent and manage patient violence in psychiatric care. The data collection took place in Finland, during August and October 2012. Inductive content analysis was used. Results: From the patients' and family members' viewpoints', meaningful activities to be organised for users' of psychiatric services were seen as an essential part of violence prevention. Humane nursing style and empathetic interaction was one of the key elements from participants' point of view in order to achieve non-violent and safe treatment environment. In addition, family members demanded possibilities to participate more actively to patient's treatment, receive up-to-date information and support from professionals of the mental health care. This could help them to participate in the demanding task of violence prevention and management. Conclusions: Both the patients and the family members suggested concrete ideas how to prevent and manage patient violence in psychiatric care. In the future, violence-related prevention and management programs in psychiatric care should include beside perspectives of the mental health professionals, also perspectives and heard voices of the patients' and their family members.